College binge drinking : personality and environment factors. - Fong, Jing Zhen. (2012)
Although binge drinkers are present in all age groups, those within the collegiate population remain as a concern to society. College students tend to engage in binge drinking behavior more often compared to their non-college peers, and their alcohol use differ from other adults in terms of its negative consequences as well as its pattern of use. Personality factors, like impulsivity and sensation-seeking, were found to be associated with college binge drinkers. Motor and cognitive impulsivity were highlighted to be positively related with college binge drinking. Motor impulsivity reflects one’s inhibiting abilities while cognitive impulsivity is the making of quick decisions. College binge drinkers often scored higher on measures measuring their motor and cognitive impulsivity. The sensation seeking trait also had a positive association with them. It has been identified that high sensation-seeking students’ purpose of binge drinking is to achieve emotional stimulation. In addition, environmental factors, like social norms, peer and media influences, also play a part in students’ binge drinking behavior. Social norms often help in guiding people behavior. Hence, students’ alcohol consumption level tends to mirror their perceived norms of drinking behavior in college. Peers also influences students’ drinking behavior, by exerting pressure on students to drink and act as a model for students to follow. In addition, media are able to shapes students’ cognition on alcohol and through that, influence students drinking patterns. As college binge drinking is different from adults’ alcoholism, it is important for authorities to curb and control the problem differently.